Changing indications and antenatal prognostic factors for ex‐utero intrapartum treatment procedures. (9th September 2022) - Porter, Hugh; Trivedi, Amit; Marquez, Miguel; Gibson, Peter; Melov, Sarah J.; Mishra, Umesh; Jani, Pranav; Cheng, Alan T.; Nayyar, Roshni; Alahakoon, Thushari I.
Abstract: Objective: In cases of suspected neonatal airway obstruction, the ex‐utero intrapartum treatment (EXIT) procedure is used to secure the airway while a fetus remains on placental circulation. We report indications and outcomes from all EXIT procedures at a tertiary obstetric unit between 1997 and 2020. Method: Retrospective cohort study with data collected from maternal and neonatal medical records. Results: Indications for EXIT procedures were micrognathia ( n  = 7), lymphatic malformations ( n  = 5), cervical teratomas ( n  = 4), goiters ( n  = 2), and intra‐oral epulis ( n  = 1). Infants with a fetal teratoma were delivered earliest due to 75% presenting with preterm premature rupture of membranes or preterm labor. Low birth weight was found in 75% of these neonates; they did not survive 1 year. Intubation at EXIT occurred for 58% ( n  = 11) of babies, and six neonates required a tracheostomy. In four cases of fetal micrognathia, the inferior facial angle (IFA) was noted to be <5th centile. All but one micrognathia case had polyhydramnios. Of the total cohort, 75% of neonates were alive at 1 year. Conclusion: Risks for neonatal demise with EXIT include fetal teratoma, low birth weight, and prematurity. Micrognathia has become an increasingly valid indication for the procedure. The combination of polyhydramnios and IFA <5% correlates well with severe airway obstruction and suggests consideration of EXIT. Key points: What's already known about this topic? Ex‐utero Intrapartum Treatment (EXIT) remains a potentially life‐saving procedure for fetuses with airway obstruction. Indications for EXIT have broadened over the past 20 years. What does the study add? Fetal teratoma, low birth weight, and prematurity should inform prenatal counseling as predictors for fetal and neonatal mortality. To improve multidisciplinary management, all neonates with suspected fetal airway obstruction should have ultrasound and MRI imaging. Micrognathia is now a common indication for EXIT. In cases of micrognathia, inferior facial angle (IFA) <5% in conjunction with polyhydramnios appears predictive of a difficult airway.